Comparison studies of tile/fiber systems manufactured from Kharkov injection molded and Kuraray SCSN-81 scintillators - Nemashkalo, A.A.; Popov, V.P.; Sorokin, P.V.; Zatserklyany, A.E.; Borisenko, A.Y.; Senchishin, V.G. (Вопросы атомной науки и техники, 2000)
We present the results from measurements of light output, light yield uniformity, and recovery after radiation damage of tile/fiber systems made from the scintillator produced by the injection molding technique in Kharkov. The tiles were trapezoidal in shape, 131x90x122 mm3, with a Kuraray Y11 multi-clad WLS read-out. The results are compared with those obtained using the tile/fiber systems manufactured from the Kuraray SCSN-81 scintillator and tested under the same conditions. The light yield uniformity is found to be improved by masking. Effects of milling, polishing, painting of tile edges and mirroring the fiber end were studied.